Opportunities and Challenges of Ecotourism in Jiri, Dolakha, Nepal - Dhakal, Bhola Nath; Pokhrel, Baijayanti Mala; Goire, Moina (RR Interdisciplinary Journal, 2024)
Tourism is a socio-cultural and economic activity and the process of spending time far from their usual surroundings for recreation and other special purposes. Ecotourism is a form of tourism where tourist travel to the natural places and responsible for conserving the environment and improving the well-being of local communities. This study has attempted to explore the opportunities and challenges of ecotourism in Jiri area of Dolakha district. Household questionnaires survey among local communities, focus group discussions and key informant interview with tourism entrepreneur, school teachers, senior citizens, local government representatives has been conducted as main primary sources of information. Furthermore, field observation and map interpretation has been also carried out. In addition to these, published articles, government documents, census data and cash study have been reviewed as secondary sources of data. It is concluded that Jiri has facing many problems including poor transportation facilities, insufficient infrastructural development for the communication, lodging, fooding, sanitation and securities for the development of ecotourism beyond to having numbers of opportunities of trekking, hiking, mountain biking, bird watching, exploring local customs and culture by visiting nearby temples and monasteries, provides breathtaking panoramic views of the mountain landscapes and Himalayas including Mount Everest and so on.